Impacts of Climate Smart Agriculture on livelihoods in sub-Saharan Africa: A Meta-analysis - Simutowe, Esau; Ngoma, Hambulo; Thierfelder, Christian (International Maize and Wheat Improvement Center, 2023)
Sub-Saharan Africa is grappling with surging food demand amid a growing population and challenges of climate change. Climate Smart Agriculture (CSA) emerges as a holistic solution, aiming to counter these complexities and enhance livelihoods. However, the evidence remains thin and mixed. We used a meta-analysis with 18 studies to assess the impacts of climate smart agricultural practices on livelihood indicators in sub-Saharan Africa. We find that adoption of climate smart agriculture is positively correlated with crop and household income and food security in sub-Saharan Africa. We found that the adoption of climate smart agriculture is associated with reduced incidences of poverty on average and improved food security outcomes. These last two findings are, however, only statistically significant at 10%, signifying the need to integrate CSA with other measures to improve food security and to reduce poverty. We can conjecture that the positive effects on incomes are not sufficient to significantly drive-up food security and poverty alleviation.